Where are they now? Long-term outcome of children with autism who received early intervention during their preschool years : a pilot study of 15 young adults - Birta Brynjarsdóttir 1987- (2016)
Objectives: The prevalence of autism in adults is constantly increasing, but little is known about their transition from childhood into adulthood. This encourages studies on how children diagnosed with autism at an early age fare later in life. The aim of this study was to examine long-term outcome of children with autism who received different forms of early intervention. Methods: Participants were 15 individuals who participated in the Iceland Young Autism Project (IYAP), affiliated to the UCLA Multi-site Young Autism Project, during the period from 1995 to 2000. Five of the participants received behavioural intervention, but the remaining 10 formed a control group and received intervention as usual. Participants were followed from their first autism diagnosis before 42 months of age (time 1) to the age of 6 years (time 2). The participants are now in their twenties (time 3). Information was gathered from parents on autism symptoms, co-occurring disorders, adaptive behaviour, functioning and participation, service use and quality of life. Results: About half of the participants have received diagnosis of a co-occurring condition and more than half take psychotropic medication. Their adaptive behaviour and quality of life is poorer than that of the general population. Hardly any differences were found between the original experimental and comparison groups. Conclusions: This study is the first to examine outcome and status of young adults with autism in Iceland. The results showed great individual variation in most variables that were measured, which suggests that although all of the participants received the same diagnosis at an early age, the outcome for them in adulthood is diverse. The difference between those who received behavioural intervention and those who did not seems to have neutralised over the years. Keywords: long-term outcome, early behavioural intervention, young adults with autism, quality of life, adaptive behaviour, co-occurring disorders